1999 Winter conference recap. - Tischler, Eric (Corrections Today, 1999)
A special section on the American Correctional Association's Winter Conference, themed “Alliances for Progress,” which was held in Nashville, Tennessee, in January 1999. Topics discussed include some of the conference's workshops and seminars on various correctional topics; award winners; keynote addresses; and proposed policies that were approved for entry into the policy process for member input.